Swelling pressure of the lumbar intervertebral discs: influence of age, spinal level, composition, and degeneration. - Urban, J; McMullin, J (1988)
The fluid content of the intervertebral disc is important in determining its mechanical response and also its transport and biologic properties. Fluid content depends on the proteoglycan content of the tissue and on the relationship of the external load to the disc's swelling pressure. The influence of proteoglycan content and external load on the hydration of nuclei from 32 human lumbar discs was measured. Swelling pressure of the same specimens was measured by equilibrium dialysis. The influence of age (14-91 years) and spinal level was noted. Proteoglycan content of the discs fell with age, and for all spines tested, proteoglycan content was lowest in the L5-S1 disc; no systematic change in collagen content was found. The hydration of the discs, as received, also fell with increase in age; in each complete lumbar spine tested, the L1-L2 and the L5-S1 discs had the lowest hydration at postmortem examination. As the stress applied to the discs was increased, hydration decreased. Although a stress of 0.10-0.23 MPa maintained the disc slices at their postmortem hydration, under a stress of about 0.6-0.8 MPa, most discs lost 40-60% of their initial fluid. The relationship between change in hydration and swelling pressure was found to depend on the composition of the disc rather than on age or degree of degeneration; the relationship between equilibrium hydration and swelling pressure could be predicted satisfactorily for a disc of known collagen and proteoglycan content.